Why people participate in collaborative consumption: an exploratory study of motivating factors in a Latin American economy - Alzamora-Ruiz, Jessica (2020)
In recent decades, collaborative initiatives have become relevant in Latin America, however, the owners of these businesses still face great challenges to mobilize consumers interest. In the research field, many collaborative consumption (CC) researchers have focused on the identification of their predictors; but studies that have explored this phenomenon via motivations perspective are very limited, especially those that focus on the Latin American context. Furthermore, these studies have analyzed on particular consumption activities and consumers with previous experience, restricting the scope of its results. To close this gap, the research has as its purpose the exploration of the motivating factors that best predict the intention to participate in CC activities into one of the three countries with the greatest number of collaborative businesses in the region. The ANOVA and CHAID are applied to a sample of 2080 people. The results reveal that, although enjoyment, sustainability, reputation and economic benefits are significant factors for CC, not all are equally effective in promoting high levels of participation in Latin American context. These findings allow to achieve a better understanding of the collaborative phenomenon, and also they contribute to the development of value proposals and more focused recruitment strategies for potential consumers in the region.